Hedysarum sunhangii (Fabaceae, Hedysareae), a new species from Pamir-Alay (Babatag Ridge - Uzbekistan) - Juramurodov, Inom; Tojibaev, Komiljon; Nikitina, Elena; Makhmudjanov, Dilmurod; Yusupov, Ziyoviddin; Deng, Tao; Dehkanov, Davron (Phytotaxa, 2021)
Hedysarum sunhangii is a new species described from the Babatag Ridge in the Uzbekistan part of the South-West Pamir-Alay (Central Asia). Morphological and molecular phylogenetic analyses were utilized to determine the taxonomic position of the species in genus Hedysarum. This new species belongs to the subsect. Crinifera of the sect. Multicaulia and it resembles H. criniferum and H. nuratense, but can be distinguished by details of its 3–4 pairs of larger and elliptical or ovate shaped leaflets, standard and keel sizes.